If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -6) = 3y + -22 Reorder the terms: 5(-6 + y) = 3y + -22 (-6 * 5 + y * 5) = 3y + -22 (-30 + 5y) = 3y + -22 Reorder the terms: -30 + 5y = -22 + 3y Solving -30 + 5y = -22 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -30 + 5y + -3y = -22 + 3y + -3y Combine like terms: 5y + -3y = 2y -30 + 2y = -22 + 3y + -3y Combine like terms: 3y + -3y = 0 -30 + 2y = -22 + 0 -30 + 2y = -22 Add '30' to each side of the equation. -30 + 30 + 2y = -22 + 30 Combine like terms: -30 + 30 = 0 0 + 2y = -22 + 30 2y = -22 + 30 Combine like terms: -22 + 30 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| 5687=47(p+40) | | 5s-7=-10+4s | | 17-(-4)= | | .06x+x=6895 | | 17-(-4)-4= | | (3x)2-10/4=54 | | 10r=80 | | 7v^2-40v-63=0 | | -25+x=-1225 | | 2x+28=x+40 | | 4/x-5=7-3/x-5 | | .4x+.5y=162 | | 3x-2(0)= | | x/3-24=-18 | | 4x+5y=162 | | 9x=-43+88 | | -14m-8=52 | | 2(3r-6)=4(r+2) | | x^2-6x+9-4y^2=0 | | (-6+3v+3x)(-2)= | | 3(0)-2=6 | | 12n=(11n)/19 | | (2x)+90=48 | | -1.5=-6/x | | 2x-22=x+3 | | 6(6v+7)-5=1+6v | | 9a-2(3a-6)=12 | | -7x+15x^2=20x | | 207=47x+-28 | | 12n=11n/19 | | 44=-6+m | | 52=x(1-x)x |